Improving Clinical Nurses’ Development of Supervision Skills through an Action Learning Approach - Irene Sommer; Karin Larsen; Carsten M. Nielsen; Britta V. Stenholt; Ida Torunn Bjørk (Nursing Research and Practice)
The aim of this study was to investigate action learning as an implementation method in a large-scale project with many participants in several autonomous and geographically spread groups. The focus of the implementation was the Model of Practical Skill Performance as a learning and supervision tool in the clinical education of nursing students. Nineteen action learning groups were established, and a total of 129 clinical supervisors and 13 facilitators were involved. To evaluate the implementation process, qualitative data were generated through three focus group interviews, questionnaires, and notes. Data illuminate clinical supervisors’ perceptions of value, impact, and sustainability when they participate in an action learning group to become familiar with the Model of Practical Skill Performance. The deductive data analysis was guided by central concepts from action learning. Action learning proved to be an engaging and effective tool in the implementation where the main strength seemed to be the autonomous local group supporting collective reflections on actions. Clinical supervisors had the right competences to adopt a reflective process-oriented approach, which is the hallmark of action learning. This study shows the necessity of collaboration between stakeholders in practice, education, and management to implement large-scale projects in clinical practice. The findings imply that managers should choose participants on the basis of their motivation and their voluntary wish to participate and that nurses’ immersion in the project over time aids implementation.